Anthocyanins extraction from purple sweet potato (Ipomoea batatas (L.) Lam) : the effect of pH values on natural color - Nhut Pham, T.; Quoc Toan, T.; Duc Lam, T; Vu-Quang, H.; Vo, Dai-Viet N.; Anh Vy, T.; Bui, Le Minh (IOP Publishing, 2019)
Anthocyanins are widely used in the food industry as safe natural colorants thanks to their benefits, attractive colors and safety for consumption. The first objective of this study was to evaluate anthocyanins extraction from Vietnam purple sweet potato (Ipomoea batatas (L.) Lam) for use as food coloring. Different extraction temperatures of solvent ethanol (40 - 70%), duration of extraction (40 - 80 min), temperature extraction (30 - 70°C) and liquid-solid ratios (4:1 - 8:1 mL/g) were selected in order to extract purple sweet potato. Second, this study examines the anthocyanin color behavior at various pH levels in aqueous solutions levels ranging from 1.0 to 14.0. At low pH (acidic conditions), anthocyanins are stable and gives a red color. Meanwhile, increasing the pH value of anthocyanin will change the color from red to pink, violet, blue, green and yellow. This variation suggested that anthocyanin could be utilized as a possible pH color indicator in commercial packaging industry and agriculture.